Anti‑nervous necrosis virus activity of the growth hormone releasing peptide‑6, GHRP‑6 - Álvarez-Torres, Daniel; Martínez, Rebeca; Moreno, Patricia; Alonso-Sánchez, María del Carmen; García-Rosado, Esther; Porras Estrada, Mario; Béjar-Alvarado, Julia (Springer Nature, 2025)
Growth hormone-releasing peptide 6 (GHRP-6), is a six-amino acid synthetic peptide that acts as a ghrelin analog and has shown growth-promoting and immunomodulatory activities in several fish species. This study evaluates the effects of GHRP-6 against the infection with the nervous necrosis virus (NNV), an important pathogen affecting the central nervous system of a wide range of fish species, including European seabass (Dicentrarchus labrax). For the in vitro evaluation, E11 cells were treated with GHRP-6 before and/or during viral infection, resulting in higher cellular survival rates, lower viral genome replication, and lower production of infective viral particles compared with control cells. These results indicate that GHRP-6 protects E11 cells from the viral infection. In order to conduct the in vivo evaluation, European seabass specimens were intraperitoneally injected with GHRP-6, resulting in the significant upregulation of several immune genes, such as TNF-A, RTP3, and IgM, in head kidney and intestine. Furthermore, NNV replication was lower in the brain from GHRP-6 injected fish than in controls, and the brain antiviral immune response was clearly modulated in treated fish. These results support the potential of GHRP-6 as an antiviral compound that could contribute to prevent viral diseases in fish farms, a priority for the aquaculture Industry
Keywords: Hormona liberadora de la somatropina; Peces; Agentes antivíricos; GHRP-6; RGNNV; Immunostimulant; European seabass; Antiviral